Adaptation of an Intervention to Reduce Disparities in School HRQOL for Latino Childhood Cancer Survivors. (31st July 2020) - Patel, Sunita K; Miranda, Leticia; Delgado, Nicole; Barreto, Nicolas; Nolty, Anne; Kelly, Natalie C; Wilson, Karla; Toomey, Debbie; Pawlowska, Anna
Abstract: Objective: Survivors of childhood leukemia, especially those from low socioeconomic status households, often experience persistent neurocognitive and academic impairment. This study adapted an existing parent training intervention to improve outcomes for low-acculturated, Spanish-speaking Latino parents of children with leukemia and pilot tested that intervention for feasibility. Methods: Semistructured interviews were conducted with a focus group of 20 Latino parents of children treated for leukemia. Ten Latino families participated in a pilot study of the adapted parenting intervention, consisting of eight sessions over 6 months. Results: Focus groups revealed that parents unanimously supported a parenting intervention but barriers to participation included time constraints, transportation issues, and anxiety in the hospital environment. The parents also highlighted cultural factors that could contribute to the health disparity, such as lack of knowledge and efficacy in facilitating their child's progress with learning and school. In the pilot study, adherence was 90%, establishing feasibility, and the adapted intervention was considered beneficial. The median parenting efficacy scores improved from preintervention to postintervention (median 3.40 vs. 3.94; p < .011), as did parent-reported school functioning of the child (median 50.00 vs. 60.00; p  = .088). Conclusions: This study addressed a health disparity by culturally adapting a parenting intervention, which was designed to improve school functioning, to meet the needs and preferences of low-acculturated, Spanish-speaking families of children with leukemia in Southern California. The pilot study demonstrated that the adapted intervention is feasible and acceptable in the target population. A larger trial is underway to test the efficacy of this adapted parenting intervention.